Analysis UI Website Design Based on Local Wisdom Visual for Green Economy Education on Javara Website - Yulianto, Arief; Gunawan, Dany Kurnia; Putri, I Gusti Ayu Agung Aristi; Keban, Kwirinov Kuma; Khaer, Ananda Fiky Dibanu (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This research analyzes the local wisdom-based user interface (UI) design on Javara Indonesia's website to support green economy education. A qualitative approach with case study method was used to explore the impact of visual elements, such as color, typography, and traditional patterns, in raising users' awareness of sustainability. Data was collected through in-depth interviews and participatory observation to identify the most effective design elements. Results show that the integration of local elements not only strengthens cultural identity, but also increases user engagement and supports digital economic literacy. In addition, the potential use of interactive technologies, such as augmented reality (AR), was identified to enrich the user experience. This research makes an important contribution to the visual communication design literature by emphasizing the importance of culture-based approaches in promoting sustainability. However, limitations of the research include the limited scope of a single case and the need for quantitative studies to further support the results. Recommendations include expanding the integration of innovative technologies and exploring cross-sector study objects to increase the impact of research on sustainable design.